A review of the Oocyclus Sharp of Ecuador with description of 12 new species (Coleoptera: Hydrophilidae: Laccobiini) - Short, Andrew E. Z.; Torres-Gavosto, Juan Martin; Hettinger, Ty (Zootaxa, 2023)
The species of the hygropetric water scavenger beetle genus Oocyclus Sharp, 1882 are reviewed for Ecuador. The genus has not previously been reported from the country. Twelve new species are described: O. ancho sp. n., O. ankas sp. n., O. bellus sp. n., O. kichwa sp. n., O. lepidus sp. n., O. packha sp. n., O. radiatus sp. n., O. rupestris sp. n., O. sumak sp. n., O. ustulatus sp. n., O. yantzaza sp. n., and O. zamora sp. n. One previously described species is newly reported for Ecuador: O. sharpi Short & Perkins 2004. There is at least one additional species that is part of a species complex that includes O. morgani García-Hernández, 2009 from Colombia and O. trujillo Short & García, 2010 from Venezuela. One new synonymy is proposed: the Venezuelan species O. zulianus Short & García, 2010 syn. n. is placed as a junior subjective synonym of O. sharpi Short & Perkins, 2004. A key to all described species known from the Andes region of South America is provided.